Post COVID-19 Unemployment Rate Prediction in India: A Machine Learning Perspective - Sainis, Nachiket; Saini, Reena (International Journal of Computer Sciences and Engineering, 2023)
Unemployment continues to be a major factor for both developed and developing countries, as a result of which they losing their overall financial and economic influence. Over the last few years, unemployment rate prediction has gained a lot of interest from researchers. The unemployment crisis has been going on for a long time. At the same time, the COVID-19 pandemic lockdown has had a devastating impact on India`s unemployment rate, with most private firms firing their staff. Predicting the growth and trend of the COVID-19 pandemic using machine learning. COVID19 is affecting lives in various ways. Unemployment is one of them. Unemployment can cause mental illness, stress, an increase in suicides, premature deaths, etc. That is why it is important to predict the pattern of unemployment in the post COVID19 situation. Machine Learning (ML) can be deployed effectively to predict the change in the unemployment rate. An ML-based model has been proposed to predict the post COVID19 unemployment rate in India. How the lockdown is affecting employment is shown and further future more effective analysis can be done by looking at various other aspects of the employment sector. The goal of our study is to look at the impact of the coronavirus on India`s unemployment rate. These models are proposed to provide the most accurate predictions for the future.